A REVISION OF PEGAEOPHYTON (BRASSICACEAE) - AL-SHEHBAZ, I. A. (Edinburgh Journal of Botany, 2000)
As delimited here, Pegaeophyton is a Sino-Himalayan genus of six species of which three, P. angustiseptatum (China), P. watsonii (India, Sikkim) and P. sulphureum (Bhutan), are described as new. P. scapiflorum var. robustum is raised to subspecific rank. Keys, detailed descriptions, and distributions are given. The affinities of Pegaeophyton are discussed.
Keywords: New taxa; Pegaeophyton; Pycnoplinthopsis; Pycnoplinthus; Sino-Himalaya